Potential of Anti-CMV Immunoglobulin Cytotect CP® In Vitro and Ex Vivo in a First-Trimester Placenta Model - Perrine Coste Mazeau; Chloé Jacquet; Clotilde Muller; Mathis Courant; Chahrazed El Hamel; Thierry Chianea; Sébastien Hantz; Sophie Alain (Microorganisms, 2022)
Background: Congenital CMV infection is the leading cause of neonatal neurological deficit. We herein studied in vitro and ex vivo the potential of the hyperimmune globulin Cytotect CP® (Biotest, Germany) for congenital infection prevention and treatment. Methods: In vitro neutralization assays were conducted in fibroblasts and retinal epithelial cells on the CMV strains TB40/E and VHL/E to determine the 50% and 90% neutralizing doses (ND50 and ND90). The toxicity was assessed by measuring LDH release. Ex vivo assays were conducted in first-trimester villi explants with the TB40/E strain, namely, neutralization assays, the prevention of villi infection, and the inhibition of viral replication in infected villi. Viability was assessed by β-HCG quantification in supernatants. Results: The in vitro neutralization tests showed that Cytotect CP®® inhibits the development of infection foci (DN50: 0.011–0.014 U/mL for VHL/E and 0.032–0.033 U/mL for TB40E) without any toxicity. In the ex vivo neutralization assays, the DN50 were 0.011 U/mL on day 7 and 0.093 U/mL on day 14. For the prevention of villi infection, the EC50 was 0.024 U/mL on day 7. Cytotect-CP® did not inhibit viral growth in infected villi. No impact on villi viability was observed. Conclusions: These results sustained that Cytotect CP® has the potential to prevent CMV congenital infection.